The Effectiveness of the Implementation of Supervisory Functions by the Inspectorate in the City of Makassar - Rahmatullah; Muhammad Syukur; Firdaus W Suhaeb (Universitas Muhammadiyah Palu, 2024)
The role of the Inspectorate in effectively and efficiently supervising and overseeing governance supports the creation of a clean and authoritative government apparatus, disciplined and organized in carrying out its duties and functions in accordance with applicable regulations. The legal basis for this is in accordance with Law No. 23 of 2014 on Regional Government, strengthened by Government Regulation No. 20 of 2001 concerning the Guidance and Supervision of the Implementation of Regional Government and Presidential Decree No. 74 of 2001 Regarding the Procedures for Supervising the Implementation of Regional Government. This research is qualitative (interviews), aiming to comprehensively reveal the events at the research site through the natural collection of data, utilizing the researcher as a key instrument to seek meaning. The current implementation of supervisory functions by the Inspectorate of Makassar City is considered ineffective. This is due to the fact that the results of the supervision are not conveyed to the Regional People's Representative Assembly (APH), so APH is not clearly informed about the performance of the Inspectorate of Makassar City in carrying out its supervisory functions. Several factors that also hinder the effectiveness of the Inspectorate of Makassar City in carrying out its tasks include human resources factors that are lacking in quantity and quality, as well as educational qualifications that do not match their duties. Additionally, infrastructure, community, and cultural factors further contribute to these challenges.